Implementasi Program Perpustakaan “KEREN” di Kelurahan Air Putih Kota Pekanbaru - Walfikri Walfikri; Zulkarnaini Zulkarnaini (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Community empowerment is a main pillar in the development of a region. Increasing public participation and services is crucial for achieving inclusive and sustainable development goals. Amid the dynamics of modern society, the role of subdistrict libraries in enhancing public services and community participation is increasingly emphasized. According to UNESCO data, the reading interest of Indonesians is very concerning, at only 0.001%. This means that out of 1,000 Indonesians, only one person regularly reads. A different study titled "World’s Most Literate Nations Ranked," conducted by Central Connecticut State University in March 2016, ranked Indonesia 60th out of 61 countries in reading interest, just below Thailand (59) and above Botswana (61).One important element in providing quality public services is the subdistrict library. As a knowledge institution and source of information, the subdistrict library has great potential to improve public services and encourage community participation. Through various programs and activities, the subdistrict library can serve as a center for information, education, and community activities relevant to the needs of the local community.